2017
DOI: 10.1111/gbb.12368
|View full text |Cite
|
Sign up to set email alerts
|

Association of AKAP6 and MIR2113 with cognitive performance in a population‐based sample of older adults

Abstract: Genetic factors make a substantial contribution to inter-individual variability in cognitive function. A recent meta-analysis of genome-wide association studies identified two loci, AKAP6 and MIR2113, that are associated with general cognitive function. Here, we extend this previous research by investigating the association of MIR2113 and AKAP6 with baseline and longitudinal non-linear change across a broad spectrum of cognitive domains in a community-based cohort of older adults without dementia. Two single n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…The rs17522122 SNP was found to be one of the genetic variants that significantly affect general fluid cognitive functioning in middle and old-age population of 53,949 individuals in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium [ 59 ]. In a recent study, the rs17522122 T allele (found in UTR-3) SNP was associated with poor performance with respect to episodic memory in older populations, as identified in the Personality And Total Health (PATH) study [ 60 ]. Thus, polymorphisms in AKAPs were found to be significantly associated with a plethora of neurological disorders in humans.…”
Section: Polymorphisms/mutations In Akaps and Other Human Diseasesmentioning
confidence: 99%
“…The rs17522122 SNP was found to be one of the genetic variants that significantly affect general fluid cognitive functioning in middle and old-age population of 53,949 individuals in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium [ 59 ]. In a recent study, the rs17522122 T allele (found in UTR-3) SNP was associated with poor performance with respect to episodic memory in older populations, as identified in the Personality And Total Health (PATH) study [ 60 ]. Thus, polymorphisms in AKAPs were found to be significantly associated with a plethora of neurological disorders in humans.…”
Section: Polymorphisms/mutations In Akaps and Other Human Diseasesmentioning
confidence: 99%
“…Prolonged expression of miR-132 causes cognitive deficiency by inhibiting acetylcholinesterase activity (Shaltiel et al, 2013); miR-182 suppresses long-term memory by interacting with actin-regulatory proteins (Griggs et al, 2013); miR-124 affects learning and memory by regulating mRNA expression of GTPase-activating protein gene (IQGAP1) (Yang et al, 2014). MiR-2113 (Andrews et al, 2017), miR-151a-3p, miR-212-3p, miR-1274b(Mengel-From et al, 2018 expression levels are associated with cognitive functioning. The study of epigenetic factors in the transgenerational transmission of cognitive abilities is promising for the development of preventive technologies of cognitive impairment in the next generations.…”
mentioning
confidence: 99%
“…Genome-wide association studies and their systematization also point to a significant role of certain microRNAs in cognitive functioning. For instance, meta-analysis of GWAS conducted in 2017 [85] identified two loci in the MIR2113 (encodes miR2113) and AKAP6 genes associated with cognitive abilities. Moreover, elderly individuals without dementia were examined in detail for the association of the variants of these genes with episodic and working memory, vocabulary, speed of perception, and reaction time.…”
Section: The Role Of Noncoding Rnas In Cognitive Developmentmentioning
confidence: 99%
“…As a result of this study, an association of rs17522122Tallele in the AKAP6 gene with reduced episodic and working memory, vocabulary, and reaction speed was reported. At the same time, the rs10457441*T-allele in the MIR2113 gene was associated with an accelerated decrease in episodic memory [85]. In 2018 [86], a study of 90 elderly monozygotic twins (aged 73-95) involved the analysis of 754 plasma-circulating microRNAs and their association with the cognitive parameters assessed with the Mini-Mental State Examination (MMSE) and Cognitive Component Score (CCS).…”
Section: The Role Of Noncoding Rnas In Cognitive Developmentmentioning
confidence: 99%